A rare cause of acute abdomen: spontaneous dissection of the superior mesenteric artery. Issue 11 (23rd September 2016) - Ansari, Mohammad Jamal Uddin; Patel, Nikunjkumar; Tulpule, Sunil; Sen, Shuvendu; Yousif, Abdalla
Key Clinical Message: Spontaneous superior mesenteric artery (SMA) dissection is a rare, but potentially fatal disease. Prompt diagnosis and treatment of SMA dissections result in a lower prevalence of intestinal infarction and mortality. In the current era, imaging techniques can promptly diagnose SMA dissection; however, no definitive guidelines have been established to treat this condition. Abstract : Spontaneous superior mesenteric artery (SMA) dissection is a rare, but potentially fatal disease. Prompt diagnosis and treatment of SMA dissections result in a lower prevalence of intestinal infarction and mortality. In the current era, imaging techniques can promptly diagnose SMA dissection; however, no definitive guidelines have been established to treat this condition.